(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2018)
This work aims to take stock of the practice pertaining to the preparation and admission of cassation appeals subject to the new regime laid down by Organic Law 7/2015. It sets out the main quantitative data for appeals filed and the systematic analysis of the criteria used for this purpose by the Admission Chamber of the Third Division of the Supreme Court as well as an assessment of their success.